Bioinspired surface structures for added shear stabilization in suction discs - Alyssa M. Hernandez; Jessica A. Sandoval; Michelle C. Yuen; Robert J. Wood (Scientific Reports)
Abstract Many aquatic organisms utilize suction-based organs to adhere to diverse substrates in unpredictable environments. For multiple fish species, these adhesive discs include a softer disc margin consisting of surface structures called papillae, which stabilize and seal on variable substrates. The size, arrangement, and density of these papillae are quite diverse among different species, generating complex disc patterns produced by these structures. Considering papillae arrangements in three fish species, the Northern Clingfish (Gobiesox maeandricus), Tidepool Snailfish (Liparis florae), and Chilean Clingfish (Sicyases sanguineus), we fabricated physical disc models that tested relevant surface pattern parameters under shear loading conditions. Parameters of interest included the area of papillae-like structures, the spacing between adjacent structures (channel spacing), and the percent coverage of elements relative to the total disc area. To create our models, a soft silicone elastomer was added to a stiff circular suction cup, which was then “stamped” using a laser-etched and thermoformed mold base to create the desired surface patterning. Discs were tested using a robotic arm equipped with a force sensor, which sheared them across smooth and rough surfaces at a fixed speed and distance. The arm was also used to vary the initial compression to test performance under both suction-dominant and friction-dominant preloads. For our designs, patterns with smaller papillae-like structures and channel spacing often produced higher peak forces than those with larger features. However, the design that withstood the highest shear load featured an intermediate pad size and channel spacing, potentially highlighting a balance between overall surface area and fluid channeling. Additionally, discs with surface patterns often outperformed the control discs (no pattern) on both smooth and rough surfaces, but performance was highly dependent on preload, with patterned discs exhibiting benefits with the higher “friction-dominant” preloads.